An effect of heat insulation parameters on thermal losses of water-cooled roofs for secondary steelmaking electric arc furnaces (Fracture and Structural Integrity, 2016)
The aim of this work is research in the insulation parameters effect on the thermal losses of watercooled roofs for secondary steelmaking electric arc furnaces. An analytical method has been used for the investigation in heat transfer conditions in the working area. The results of the research can be used to choose optimal cooling parameters and select a suitable kind of insulation for water-cooled surfaces.
Keywords: Electric arc furnaces; Heat transfer; Mathematical modeling; Water-cooled roofs